Infusing data analytics and sustainability into accounting curriculum / Zhou Chenyuan - Zhou , Chenyuan (2023)
Nowadays, universities have become an important place to train accounting practitioners who can contribute to the economy and market demand. On the one hand, accounting students are required to have advanced skills such as data analytics skills and sustainable thinking that can help enterprises; On the other hand, it also puts forward higher requirements for accounting educators in universities. They need to set up appropriate and helpful courses to help students acquire this knowledge. These accounting educators must clarify the critical contents of the taught topics, set up courses, and use appropriate teaching methods. Therefore, this study aims to explore what data analytics skills and sustainability topics should be included in the university accounting curriculum, where data analytics skills and sustainability topics should be set, and what teaching methods should be used. Then, it also tested whether educators and institutions with different characteristics would have differences and specific differences in designing the two courses. Finally, this study also tested the relationship between educators' teaching experience and knowledge level and the design of these two courses. This study adopts quantitative research methods, collects the views and suggestions of accounting educators in Chinese universities through a questionnaire, then analyses their answers, and finally draws a conclusion. The survey results show that accounting educators believe that when teaching data analytics, the most important thing is to cultivate students' data analytics ability and critical thinking; When teaching environmental sustainability, educators should focus on management and cost accounting, external reporting and auditing. When teaching social sustainability, educators should focus on Socioeconomic Compliance and Marketing & Community. As for the answer to where to set up these two types of courses, educators believe that whether they are set separately or integrated into the existing courses, they need the cooperation of other disciplines inside and outside the business school; Finally, for the choice of teaching methods, most educators believe that case study and practice should be used. The choice of design courses varies between educators of different genders, and teaching experience and knowledge level are indeed related to some dimensions of design courses. This research fills the gap in teaching data analytics and sustainability in accounting education in developing countries, especially in China. In terms of practical implications, the research findings provide guidance and suggestions for Chinese universities and other developing countries to set up these two kinds of courses in the accounting curriculum. However, because the conclusion of this study is based on a specific period of time and the number of participants is limited, the research results of this study should be expanded to a greater extent in order to have more universal guiding significance.